Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2746/0425164044877314
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal (ICC) in equine colic: an immunohistochemical study of horses with obstructive disorders of the small and large intestines

Abstract: SummaryReasons for performing study: The gastrointestinal pacemaker cells, the interstitial cells of Cajal (ICC), have been implicated in several human gastrointestinal dysmotility syndromes. Recently, the involvement of these cells in equine gastrointestinal diseases has been investigated in cases of equine grass sickness where a significant reduction in ICC density was observed. Objective: To investigate ICC density in equine obstructive gastrointestinal disorders using immunohistochemical labelling methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 37 publications
3
50
1
3
Order By: Relevance
“…Conversely, in the horse study of Pavone et al (2012), it was suggested that the enteric nervous system and ICC changes observed may have been secondary to the colic episodes. Fintl et al (2004) suggested that the ICC changes in horse large intestinal obstructive disorders may have been a possible cause rather than effect of the colic episodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, in the horse study of Pavone et al (2012), it was suggested that the enteric nervous system and ICC changes observed may have been secondary to the colic episodes. Fintl et al (2004) suggested that the ICC changes in horse large intestinal obstructive disorders may have been a possible cause rather than effect of the colic episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Horses with chronic obstructive disorders of the large colon or recurrent caecal impactions have been shown to have reduced densities of neurons in the large colon or caecum (Schusser and White, 1997;Schusser et al, 2000). Additionally, a reduction in ICC density has been demonstrated in the pelvic flexure of horses with large intestinal obstructive disorders, suggesting a possible involvement of ICC in equine intestinal dysmotility (Fintl et al, 2004). Recently, a reduction in enteric neuronal activity and ICC immunoreactivity in cases of colic in horses has been reported (Pavone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With TTX treated equine jejunal muscle strips show spontaneous contractions (basal contractility) mediated by the electric pacemaker function of ICCs (Takaki 2003, Fintl et al 2004) without any neuronal participation. These spontaneous contractions can be defined by amplitude (isometric force of contraction, mN) and by frequency (peaks/min).…”
Section: Measurement Of Basal Contractile Activitymentioning
confidence: 99%